Electromyographic Evaluation of neck Muscle Activity on Postural Changes in Class II Patients with Vertical Growth Pattern Undergoing Twin Block Appliance Therapy – An Observational Study - Adhikari, Manoj; Jha, Kanistika (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Variations in facial skeletal morphology can influence electromyographic activity in masticatory, neck, and trunk muscles. While Twin Block Appliance therapy has been shown to alter the neuromuscular pattern of the masseter and temporalis muscles, there is a lack of literature on its effects on neck muscles and postural changes in the mandible. This study aims to assess the electromyographic activity of neck muscles before and after Twin Block Appliance therapy in growing patients with Class II malocclusion and hyper-divergent growth patterns. Methods: A study was conducted on 15 growing patients (aged 9-14 years) diagnosed with skeletal Class II malocclusion and hyper-divergent growth patterns, who were undergoing Twin Block Appliance therapy. Bilateral electromyographic activity of the Sternocleidomastoid and Trapezius muscles was recorded using bipolar surface electrodes. Measurements were taken during postural rest position, maximum voluntary clenching, and neck movements at the initiation of treatment and subsequently at 1, 3, 6, and 9 months of Twin Block Appliance therapy. Results: The changes in electromyographic activity of neck muscles were assessed using analysis of variance and a paired t-test. During the postural rest position and neck movement, the electromyographic activity of the Sternocleidomastoid and Trapezius muscles showed a tendency to decrease from baseline to the end of treatment; however, these changes were not statistically significant. Additionally, there was a non-significant increase in neck muscle electromyographic activity during maximum voluntary clenching. Conclusion: Twin Block Appliance therapy does not significantly impact electromyographic activity of the Sternocleidomastoid and Trapezius muscles in patients with hyper-divergent Class II malocclusion.